Smart power systems and smart grids : toward multi-objective optimization in dispatching - Lu, Qiang, 1936-; Chen, Ying; Zhang, Xuemin, Ph. D. (De Gruyter, 2022)
The book systematically introduces smart power system design and its infrastructure, platform and operating standards. It focuses on multi-objective optimization and illustrates where the intelligence of the system lies. With abundant project data, this book is a practical guideline for engineers and researchers in electrical engineering, as well as power network designers and managers in administration.